Leadership from the Perspective of Legitimacy and Participation - Chrobak, Karol (Roczniki Filozoficzne, 2025)
The article analyses Jarosław Kucharski’s book Etyka przywództwa (The Ethics of Leadership, Kraków 2021). The starting point of the discussion is the author’s critical observation that Kucharski’s exclusive focus on the leader–follower relationship leads to the marginalization of the active role of followers in the decision-making process. In response, the author proposes to complement the analysis of leadership with the follower’s perspective, particularly in terms of the legitimacy of leadership and participation in the decision-making process. The analysis addresses both formal and qualitative aspects of the legitimacy of leadership, emphasizing its processual character. It also outlines direct and indirect forms of participation, including models of representation with broad and narrow scopes of involvement. The article highlights the differences between business and political leadership considering the categories of legitimacy and participation. In this context, democratic leadership is identified as a model characterized by a decentralized structure. In conclusion, the author argues that the omission of legitimacy and participation in Kucharski’s analysis fails to account for contemporary trends in management, which increasingly conceive of leadership as a multicentred, consultation-based process.